Acceptance and Use of the MyASN Application Among Civil Servants: An Integration of TAM and IS Success Model in South Central Timor Regency - Merlyn Gizella Nifu; Wiwin Sulistyo; Hendry Hendry (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2026)
The MyASN application is a mobile-based mandatory system designed to support Civil Servants (ASN) in accessing personnel-related information. However, its implementation still faces challenges, including data inconsistencies and system integration issues. This study analyzes the factors influencing the acceptance and actual use of the MyASN application among civil servants in South Central Timor Regency. The research integrates the Technology Acceptance Model (TAM) and the DeLone and McLean Information Systems Success Model. A quantitative survey involved 250 respondents, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS. The results reveal a distinct adoption pattern for mandatory government systems. Service quality has no significant impact on user perceptions, indicating that users prioritize independent system functionality over technical support. System quality acts as a baseline expectation that significantly enhances perceived ease of use and perceived usefulness, but it does not significantly influence user satisfaction. Conversely, information quality emerges as the application's true core value; while it does not affect ease of use, it strongly drives perceived usefulness and user satisfaction. Furthermore, user satisfaction acts as the strongest predictor of users’ intention to continue using the application, which directly drives actual system use. Practically, these findings recommend that the National Civil Service Agency (BKN) and regional governments prioritize data accuracy to achieve user satisfaction and maintain system stability to prevent user dissatisfaction, rather than solely focusing on support services.